Study of a cutaneous leishmaniasis outbreak in General Vedia, Province of Chaco, 1996 - Salomón, Oscar Daniel (2001)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.